Core–shell structured nanospheres for photothermal ablation and pH-triggered drug delivery toward synergistic cancer therapy. Issue 43 (18th May 2017) - Zhong, Tian; Fu, Jia; Huang, Ran; Tan, Lianjiang
Abstract : Core–shell CuS(DOX)@CS nanospheres with pH-responsive drug release ability and photothermal conversion properties are synthesized for synergistic cancer therapy. Abstract : CuS nanoparticles capped with a long-chain carboxylic acid were synthesized and conjugated with chitosan (CS) via N -hydroxysuccinimide. The anticancer drug doxorubicin (DOX) was then encapsulated by hydrophobic interaction, producing pH-responsive CuS(DOX)@CS nanospheres with photothermal conversion properties for controllable drug release and photothermal ablation (PTA). On the one hand, the encapsulated CuS nanoparticles can absorb NIR photons and be heated efficiently. On the other hand, the entrapped DOX can be released from the swollen CuS(DOX)@CS nanospheres caused by stretched oleoyl-CS chains at lowered pH. Combining chemotherapy and PTA, the biocompatible CuS(DOX)@CS nanospheres can provide synergistic cancer treatment, as evidenced by both in vitro and in vivo experiments. This study gives new insights into developing multifunctional drug delivery agents for cancer nanotherapeutics.